Factors determining the success of small and medium scale entrepreneurs. - Pushpanathan, A. (Wayamba University of Sri Lanka., 2018)
There is a broad consensus that a vibrant small and medium scale enterprise is one of the principal driving forces in the development of a market economy and vital for a healthy economy. The men and women who run these enterprises are called entrepreneurs. Entrepreneurship is a company that undertakes new arrangement to produce new products and services. The small and medium scale Enterprises make up a large part of Sri Lankan economy. The entrepreneurs provide employment opportunity to the different skills, skilled, semi-skilled, and unskilled people. The present study is to analyze the factors influencing the success of Small and Medium Scale Entrepreneurs in Vavuniya District. The main objective of the present study is to examine the factors determining the success of small and medium scale entrepreneurs in Vavuniya District. The determining factors – marketing factors, technological factors, financial factors, good management, personal quality – considered as independent variables and success of entrepreneurs considered as dependent variable of the study. The researcher identified the 100 entrepreneurs from the database in the Chamber of Commerce in Vavuniya district as the sample of the present study. Primary and Secondary data were collected for this study purpose and questionnaires were issued among the entrepreneurs for collecting the data. The data were analyzed by using the SPSS version 20. For testing the hypotheses, the Correlation analysis was discussed. The results indicated that the all factors are positively correlated with the success of entrepreneurs in Vavuniya District. The finding indicated that the Marketing factors has the higher correlation relationship with the success of entrepreneurs than the other factors.
Keywords: Entrepreneurs.; Financial factor.; Marketing factor.; Technological factor.